Implementing collaborative care to reduce depression for rural native American/Alaska native people - Deborah J. Bowen; Diane M. Powers; Joan Russo; Robert Arao; Erin LePoire; Earl Sutherland; Anna D. H. Ratzliff (BMC, 2020)
Abstract Background The purpose of this study was to identify the effects of Collaborative Care on rural Native American and Alaska Native (AI/AN) patients. Methods Collaborative Care was implemented in three AI/AN serving clinics. Clinic staff participated in training and coaching designed to facilitate practice change. We followed clinics for 2 years to observe improvements in depression treatment and to examine treatment outcomes for enrolled patients. Collaborative Care elements included universal screening for depression, evidence-based treatment to target, use of behavioral health care managers to deliver the intervention, use of psychiatric consultants to provide caseload consultation, and quality improvement tracking to improve and maintain outcomes. We used t-tests to evaluate the main effects of Collaborative Care and used multiple linear regression to better understand the predictors of success. We also collected qualitative data from members of the Collaborative Care clinical team about their experience. Results The clinics participated in training and practice coaching to implement Collaborative Care for depressed patients. Depression response (50% or greater reduction in depression symptoms as measured by the PHQ-9) and remission (PHQ-9 score less than 5) rates were equivalent in AI/AN patients as compared with White patients in the same clinics. Significant predictors of positive treatment outcome include only one depression treatment episodes during the study and more follow-up visits per patient. Clinicians were overall positive about their experience and the effect on patient care in their clinic. Conclusions This project showed that it is possible to deliver Collaborative Care to AI/AN patients via primary care settings in rural areas.